Comparison of Irrigation Fluids In 3rd Molar Surgery: Fluids-Normal Saline, Normal Saline + Betadine, Normal Saline + Chlorhexidine - Vinit Mahure, Ishani; Gondhalekar, Rajashree; Kolhe, Vivek; Vijay Gulhane, Shreyash; Prasanna Ghotane, Atharva; Khuba Chavan, Arthi (Journal of Neonatal Surgery, 2025)
Aim: To compare the effectiveness of different irrigation fluids—Normal Saline, Normal Saline with Povidone-Iodine (Betadine), and Normal Saline with Chlorhexidine—in reducing postoperative complications such as pain, trismus, infection, and alveolar osteitis following impacted mandibular third molar surgery. Materials and methods: A total of 60 participants were randomly divided into three groups (n=20 per group) based on the final irrigant used after tooth removal. Group A received 0.9% normal saline, Group B received a combination of normal saline and 0.5% povidone-iodine (Betadine), and Group C received normal saline with 0.12% chlorhexidinegluconate. All procedures were performed under local anesthesia using 2% lignocaine with 1:80,000 adrenaline. A full-thickness mucoperiosteal flap was elevated, followed by bone guttering and tooth sectioning using saline as the standard coolant. Data analysis was done using SSPS software. Results: In our study, a total of 60 patients were enrolled and equally divided into three groups: Group A (Normal Saline), Group B (Normal Saline + Betadine), and Group C (Normal Saline + Chlorhexidine), with 20 patients in each group. The mean age was comparable among the groups, recorded as 26.4 ± 4.2 years in Group A, 25.8 ± 3.9 years in Group B, and 26.1 ± 4.5 years in Group C. Gender distribution included 29 males and 31 females, with Group A comprising 11 males and 9 females, Group B with 10 males and 10 females, and Group C with 8 males and 12 females. Most participants (n = 47) were categorized as ASA I, while the remaining 13 were ASA II; Group A had 16 ASA I and 4 ASA II patients, Group B had the same distribution, and Group C included 15 ASA I and 5 ASA II. Mouth opening was measured in millimeters at three time points: preoperatively, postoperative day 1, and postoperative day 7. The preoperative values were similar across groups—16.6 ± 4.5 mm in Group A, 16.9 ± 1.7 mm in Group B, and 17.3 ± 1.8 mm in Group C (p = 0.472). On postoperative day 1, an increase in mouth opening was noted in all groups: 22.9 ± 5.7 mm in Group A, 25.1 ± 1.9 mm in Group B, and 26.2 ± 1.2 mm in Group C, showing a statistically significant difference (p = 0.004). By postoperative day 7, further improvement was seen—44.21 ± 3.5 mm in Group A, 45.1 ± 1.4 mm in Group B, and 45.9 ± 0.9 mm in Group C (p = 0.016). Intragroup comparisons also demonstrated statistically significant improvements over time (p < 0.05). Conclusion: Chlorhexidine irrigation showed slightly better improvement in postoperative mouth opening compared to betadine and normal saline.